Death, Ghosts, and Spiritual Tourism: Conceptualizing a Dark Spiritual Experience Spectrum for the Paranormal Market - Ironside, Rachael (Journal of Scientific Exploration, 2023)
Paranormal tourism is a lucrative market offering visitors the opportunity to engage with enchanting experiences and stories in destinations around the world. Specifically, ghost tourism connects people to the dead (and death) through dark narratives, supernatural legends, and participatory experiences. Previous scholarship has suggested that ghost tourism exhibits characteristics of dark tourism (by visiting dark places) and spiritual tourism (by engaging in spiritual practices); however, this relationship has not been fully explored. The purpose of this conceptual paper is to consider where the experiential and motivational characteristics of dark, spiritual, and paranormal tourism converge, and to consider whether this convergence produces a dark spiritual experience for consumers. Three dimensions are identified as contributing towards the degree of dark experience offered by ghost tourism: place, promotion and production, and participation. To conclude, a Dark Spiritual Experience Spectrum is proposed, illustrating the characteristics of each dimension and their influence on the degree of dark spiritual experience offered to consumers. It is argued that these dimensions have the potential to impact the tourist experience, influence visitor motivations, and, consequently, drive an evolving paranormal market.